A vaginal drug delivery model. (12th October 2016) - Mirza, Mohd. Aamir; Panda, Amulya K.; Asif, S.; Verma, Devina; Talegaonkar, Sushama; Manzoor, Nikhat; Khan, Amber; Ahmed, Farhan Jalees; Dudeja, Mridu; Iqbal, Zeenat
Abstract: Efficient drug delivery at vaginal cavity is often a challenge owing to its peculiar physiological variations including vast differences in pH. Keeping in view this attribute of the target site, the current work was aimed at developing formulation strategies which could overcome this and successfully deliver molecules like itraconazole through SLNs. Optimized SLNs with the given composition was selected for further development into mucoadhesive and thermosensitive gel. Stearic acid and Compritol 888 (1:1, w/w ratio) as lipid, a mixture of 3% Poloxomer 188 and 0.5% sodium taurocholate as surfactant and organic to aqueous ratio of 10:50 was taken. Carbopol 934 and Pluronic F 127 were taken for the development of gel. Optimized gel exhibited a desired gelling temperature (35 °C); viscosity (0.920 PaS) and appreciable in vitro drug release (62.2% in 20 h). MTT assay did not show any cytotoxic effect of the gel. When evaluated in vivo, it did not exhibit any irritation potential despite appreciable bioadhesion. A remarkable decrease in CFUs was also observed in comparison with control and marketed formulation when evaluated in rat infection model. Thus, the proposed study defines the challenges for developing a suitable formulation system overcoming the delivery barriers of the vaginal site.